The Shared Montage in "The Year of the Discovery" (2020) - Calatayud Fernández, Priscila (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
The proposal of the feature film by Luis López Carrasco, The Year of the Discovery (2020) —winner of the Goya for Best Editing and Documentary— has joined the genre of peninsular experimental documentary with a unique reflection on the history of labor struggle in the late 20th century. The creativity in its editing proposal has elevated this hybrid film to a cult status in the Spanish national territory. López Carrasco portrays the protests against factory closures in Cartagena during the 90s by exploring boundaries, division, and distribution through editing, halfway between fiction and non-fiction. In this essay, I argue that the editing, which I have termed shared, develops a complex reflection on the community through its formal exploration. Specifically, the use of the split screen engages with the concept of “partage” by the French philosopher Jean-Luc Nancy. It materializes, through the aesthetics of its audiovisual universe, the fragmentation that characterizes the ontology of being-in-common as outlined by Nancy in his essay The Inoperative Community ([1983] 2001). This article reflects on how exploring the boundaries of the documentary genre through split screen unfolds dynamics of incompleteness that result in a counter-hegemonic and counter-teleological proposal. Ultimately, my cultural analysis shows that The Year of the Discovery not only challenges the political-economic imaginary that underpins the transition from late Francoism to democracy but also reveals the shared, fragile, and finite condition of social experience.
Keywords: Luis López Carrasco; Montage; Split Screen; Cartagena; Spanish Industrial Reconversion; Inoperative Community; Partage